INITIATIVE CLASS DIDACTIC MATERIALS AND TEACHING METHODS - Paluanova Hurliman; Paluanova Aynakhan (ОБРАЗОВАНИЕ НАУКА И ИННОВАЦИОННЫЕ ИДЕИ В МИРЕ, 2023)
Annotation: This article talks about the methods of teaching didactic materials in primary classes.